Argumentos sobre o "Por que ensinar Matemática na Escola" na concepção de diferentes atores da Educação Matemática - Silva, Máxima Aparecida de Oliveira (2005)
This report purpose is to research how distinct actors in Mathematics education think about what are the motivations to find Mathematics in basic education courses. It makes use of bibliography and documental researches over and above half structural interviews. The researcher s questions that guide this report are: with regard to Math s knowledge s, what are the important characteristics that make it different from other acquirements? Why is the Mathematics an obligatory subject matter in school as much in elementary school as in high school in all schools systems? Is Math Knowledge useful? How can we justify the importance of the contents in official teaching programs of Math? What are the arguments that justify the teaching of Math in schools? Analyzing all information collected we conclude that Mathematics is one way how human-beings can express their feelings besides a powerful instrument to perceive the World around, however it s clear that there are a lot of possible approaches to justify its teaching in schools. Without any question Mathematics is very important, but it s necessary to look up on education s courses curriculums the social prominence from what we intend to teach.